The Management of Fear by the Spanish Catholic Church in the Textbooks of Religion: Changes and Continuities resulting from the Second Vatican Council - Castillejo Cambra, Emilio (Historia y Memoria de la Educación, 2015)
This article uses ecclesiastical records and textbooks of Religion to make comparisons regarding the way in which the Spanish Catholic Church administered the emotion of fear before and after Vatican Council II. We see evidence of the erosion of natural fears: epidemics, hunger, war... (the humanization of God does not seem compatible with his anger), of scatological fears, where the sensory elements of fear weigh most heavily (the repoliticization of the Catholic religion increasingly puts fear in more profane places), or even the fear of the non-Catholic other (ecumenism). But the texts also corroborate, especially in the neo-integrationist Church manuals, the perseverance of other induced fears, where the cognitive elements of fear are clearly imposed: fear of the secularization of science and of thought, of the loss of the Church’s influence in society, of the reforms coming from Vatican Council II, of the theology of liberation, of secularism or of the loss of the state protection that the Spanish Catholic Church had always enjoyed. As a result we find it contentious to state, as some authors do, that the Vatican Council II signaled a change from a Stateoriented institution to a society-oriented one.